High pressure phase equilibrium of the system containing carbon dioxide, chloroform and globalide, and characterization of thermodynamic properties of e-caprolactone, globalide and w-pentadecalactone - Girardi, Davi Gustavo Lisboa (2022)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2022.